Ontogenesis, structure and ultrastructure of Hymenaea stigonocarpa (Fabaceae: Caesalpinioideae) colleters - Paiva, Élder Antônio Sousa; Machado, Silvia Rodrigues [UNESP] (Universidad de Costa Rica, 2006)
The genus Hymenaea is characterized by a great diversity of secretory structures, but there are no reports of colleters yet. The objectives of this study are to report the occurrence and describe the origin and structure of colleters in Hymenaea stigonocarpa Mart. ex Hayne. Shoot apex samples were collected, fixed, and processed for light microscopy, scanning electron microscopy, and transmission electron microscopy as per usual methods. Colleters occur predominantly on the stipule’s adaxial side. These structures are found at the base on a narrow strip, corresponding to the median vein up to half the length of the stipule. When present on the abaxial side, they are concentrated at the base and restricted to the margins. Colleters develop from the protoderm; they are elongate and club-shaped. Their body has no stratification; their surface cells differ from the inner cells only in position and presence of cuticle. Colleter cells have thin walls, dense cytoplasm, large nuclei, many mitochondria, rough endoplasmic reticulum, and abundant dictyosomes. Histochemical tests with Ruthenium red showed pectic compounds in the cytosol. In H. stigonocarpa, colleter arrangement is compatible with the hypothesis that they protect shoot apex. In this species, protection is reinforced by the sheath formed by the stipule pairs.
Keywords: Colleter; Secretion; Stipule; Ultrastructure; “Cerrado” vegetation